2022
DOI: 10.3390/ma15207282
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Strength and Durability Properties of Wooden Ash Based Concrete

Abstract: The partial replacement of cement in concrete with other building materials has come to light because of research on industrial waste and sustainable building practices. Concrete is made more affordable by using such components, and it also helps to ease disposal worries. Ash made by burning wood and other wood products is one example of such a substance. Many researchers focused on the utilization of wooden ash (WA) as a construction material. However, information is scattered, and no one can easily judge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Therefore, from the results of the slump test and the air content test, it can be said that WBA concrete has a slump and air content without any problems in construction. These facts are consistent with those described in [7,15,16].…”
Section: Slump and Air Content Of Wba Concretesupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, from the results of the slump test and the air content test, it can be said that WBA concrete has a slump and air content without any problems in construction. These facts are consistent with those described in [7,15,16].…”
Section: Slump and Air Content Of Wba Concretesupporting
confidence: 93%
“…As reported in [7,15,16], woody ash mixed into the concrete may absorb water and the workability of concrete may decrease. Therefore, when woody ash is mixed into the concrete, it is necessary to increase the unit water volume in concrete in order to achieve the same level of workability as normal concrete.…”
Section: Concrete MIX Designmentioning
confidence: 84%
“…Kim [49] highlighted the latest breakthroughs in cement and concrete research, including novel strategies for lowering carbon dioxide emissions in Portland cement production, such as the development of new building materials [50], and the development of mathematical modeling of the reliability of new composite materials [51]. Furthermore, it is necessary to highlight the importance of the prediction of the performance properties and reliability of new building materials [52].…”
Section: Methods To Estimate the Carbon Dioxide Removals Due To Carbo...mentioning
confidence: 99%
“…Furthermore, it is necessary to highlight the importance of the prediction of the performance properties and reliability of new building materials [52]. For instance, AL-Kharabsheh et al [50] suggested the partial replacement of Portland cement clinker in cement with wooden ash and studied its effect on concrete compressive strength and durability, concluding that 10% is the optimum replacement.…”
Section: Methods To Estimate the Carbon Dioxide Removals Due To Carbo...mentioning
confidence: 99%
“…Analyzing the process of processing walnut shells to obtain organic coarse aggregate for concrete, we can conclude that, despite the use of water in it and taking into account the potential energy costs for its heating, it is much more environmentally friendly and less energy-intensive than the production of a mineral coarse-aggregate placeholder. It is also important to note that, as mentioned above, the walnut shell is a rapidly renewable natural raw material for which the issue of mass disposal has not been resolved, while mineral aggregates are exhaustible and non-renewable resources that require energy-intensive and environmentally unsafe technological processes for production [ 23 , 24 , 25 , 26 , 27 , 28 ]. The work of the authors [ 21 ] is devoted to the study of the mechanical properties of concrete with the partial replacement of coarse aggregate with walnut shells and partial replacement of fine aggregate with metallurgical slag.…”
Section: Introductionmentioning
confidence: 99%